MENUMBUHKAN EKOSISTEM LITERASI DI MI AL-MAHMUD KUMPULREJO 01 MELALUI PROGRAM GERAKAN LITERASI SEKOLAH (GLS) - Al Wiyah, Naili Amani; Mashlihatul Umami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Literacy is an important foundation for successful learning in basic education. Schools have a strategic role in fostering a culture of literacy through the creation of a conducive literacy ecosystem, one of which is through the School Literacy Movement Program (GLS). This study aims to describe the implementation of GLS at MI Al-Mahmud Kumpulrejo 01 in fostering a literacy ecosystem, identifying the obstacles encountered, and examining the school's efforts to overcome them. This study uses a qualitative approach with a descriptive research type. Data were collected through observation, interviews with the principal, teachers, and students, as well as documentation studies. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that GLS has been implemented through reading habits before learning, the provision of reading corners in classrooms, and the use of non-curricular reading books. However, the implementation of the program has not been fully consistent and integrated into learning. The school literacy ecosystem has begun to take shape, but it still needs to be strengthened, especially in terms of teacher involvement, the availability of varied reading materials, and literacy program management. The school has made various development efforts, such as encouraging the role of teachers, adding literacy facilities, and planning program evaluations. This study confirms that GLS has the potential to foster a sustainable literacy ecosystem if it is managed systematically and collaboratively.